Intracellular reactive oxygen species scavenging effect of fucosterol isolated from the brown alga Sargassum crassifolium in Vietnam - Chi, Hoang Kim; Cuong, Le Huu; Van, Nguyen Thi Hong; Hang, Tran Thi Nhu; Nghi, Do Huu; Duc, Tran Mai; Huong, Le Mai; Ha, Tran Thi Hong (Vietnam Journal of Marine Science and Technology, 2020)
Sargassum is a widely distributed marine brown algal genus in Vietnam and has been considered a source of diverse bioactive metabolites. In this study, S. crassifolium collected from South Central region of Vietnam was chemically studied and bioactively evaluated. Fucosterol was isolated and identified from the methanolic extract of the alga by means of chemical fractionation and spectral analysis and showed no cytotoxic effect in Hep-G2 cells at the observed concentrations. In vitro assay for intracellular reactive oxygen species by dichlorofluorescein method revealed a potent scavenging effect of the isolated compound. Accordingly, the level of intracellular reactive oxygen species induced by hydrogen peroxide (H2O2) was reduced by 71.66% with the treatment of fucosterol at 10 µg.ml-1. The results indicated the ability of algal fucosterol in diffusing into cells and preventing the production of different ROS compounds and further suggested the therapeutic potential against diseases caused by oxidative stress of natural metabolites from S. crassifolium in Vietnam.